2020
DOI: 10.1016/j.cell.2020.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Aralar Sequesters GABA into Hyperactive Mitochondria, Causing Social Behavior Deficits

Abstract: Highlights d Mitochondrial activity regulates the availability of the neurotransmitter GABA d The mitochondrial transporter Aralar is necessary for GABA uptake d Mitochondrial dysfunction in Drosophila Cyfip mutants affects social behavior d Social deficits are rescued by modulation of GABA levels and mitochondrial activity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 174 publications
(212 reference statements)
3
65
1
Order By: Relevance
“…Our observations of reduced number, but normal volume, of presynaptic mitochondria in Cyfip2 +/− neurons contradict the results of a recent report showing increased mitochondrial activity and size in Drosophila Cyfip mutants [13]. Only one Cyfip gene exists in Drosophila, but there are two genes, Cyfip1 and Cyfip2, in mice.…”
Section: Main Textcontrasting
confidence: 97%
“…Our observations of reduced number, but normal volume, of presynaptic mitochondria in Cyfip2 +/− neurons contradict the results of a recent report showing increased mitochondrial activity and size in Drosophila Cyfip mutants [13]. Only one Cyfip gene exists in Drosophila, but there are two genes, Cyfip1 and Cyfip2, in mice.…”
Section: Main Textcontrasting
confidence: 97%
“…Cognitive impairment is a common feature in adults presenting with mitochondrial encephalopathy, such as MELAS (mitochondrial encephalopathy lactic acidosis, and stroke-like episodes) (8) and psychiatric symptoms are associated with MDs in up to 70% of the adult population (9,10). Along the same lines, a recent article suggested that mitochondrial activity could regulate the availability in neurons of GABA, an inhibitory neurotransmitter, leading to social deficits that can be rescued by the modulation of GABA level (11).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it is reported that Aralar1 is responsible for uptake of GABA into mitochondria that is activated by mitochondrial membrane polarization. Interestingly, heterozygous aralar1 mutant flies exhibit decreased competition for food and grooming and hyperactivity, indicating a role in social activity [ 123 ]. The aralar1 gene is orthologous to the human SLC25A12 and S LC25A13 genes.…”
Section: Drosophila Epilepsy Modelsmentioning
confidence: 99%